Thursday, 29 November 2012

Implementation of Full Adder using Half Adder


By on 01:18

In this post I explain how to construct full adder with the help of half adder.





Truth Table:-



A B C S1 C1 Sum C2 Cout
0 0 0 0 0 0 0 0
0 0 1 0 0 1 0 0
0 0 0 1 0 1 0 0
0 0 1 1 0 0 1 1
1 1 0 1 0 1 0 0
1 1 1 1 0 0 1 1
1 1 0 0 1 0 0 1
1 1 1 0 1 1 0 1



Sum=A'(B'C+BC')+A(B'C'+BC)
=A'(B⊕C)+A(B⊕C)'

Let x=B⊕C
=A'x+Ax'
=A⊕x
=A⊕B⊕C

Cout=A'BC+AB'C+ABC'+ABC=AB+BC+AC



If you have any query then leave your comments and don't forgot to follow me on Google+,Facebook,Twitter.

0 comments:

Post a Comment

Related Posts Plugin for WordPress, Blogger...